1989
DOI: 10.1902/jop.1989.60.2.104
|View full text |Cite
|
Sign up to set email alerts
|

Nitrendipine–Induced Gingival Overgrowth in Dogs

Abstract: This study assessed the development of gingival overgrowth in dogs given nitrendipine, a new antihypertensive dihydropyridine. Nine male Beagle dogs with established plaque and gingivitis were used. Following a baseline examination, which involved assessment of plaque, gingivitis, and gingival enlargement, six dogs (test) received nitrendipine twice daily in a high dose, while 3 dogs (control) received placebo. Clinical scorings were repeated after 10 and 20 weeks. At termination of the study gingival biopsies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…This potential effect of DRM was supported by evidence of gingival changes seen in dogs during long-term study, a finding characteristic of some classes of calcium channel blockers in animals and humans (Heijl and Sundin, 1989;Ellis et al, 1999;Missouris et al, 2000). In vitro binding studies indicated a low calcium channel blockade by casopitant and M13, M12, and M31.…”
Section: Discussionmentioning
confidence: 73%
“…This potential effect of DRM was supported by evidence of gingival changes seen in dogs during long-term study, a finding characteristic of some classes of calcium channel blockers in animals and humans (Heijl and Sundin, 1989;Ellis et al, 1999;Missouris et al, 2000). In vitro binding studies indicated a low calcium channel blockade by casopitant and M13, M12, and M31.…”
Section: Discussionmentioning
confidence: 73%
“…However, the observed areas in their studies were buccal and lingual (not approximal), different from our areas (approximal). As stated above, gingival overgrowth occurs mostly in approximal areas, since bacterial plaque readily accumulates between teeth and can cause inflammation (16,24,25). Considering these, approximal gingival tissues could be more susceptible to gingival overgrowth due to the infiltration of inflammatory cells.…”
Section: Discussionmentioning
confidence: 97%
“…[15] Gingival overgrowth has been reported in 1-10% of the patients on calcium channel blockers. Ramon et al, 1984, [16] and Shaftic et al, 1986, [17] reported prevalence of overgrowth as 0.5-83% for nifedipine and 74% for diltiazem; whereas, Miller and Damm (1992) have observed 4% enlargement with verapamil therapy. [18] Some of the calcium channel blocker prescribed for different cardiovascular aliments are listed below and have been found to cause enlargement of gingiva.…”
Section: Nifedipine-induced Gingival Hyperplasiamentioning
confidence: 97%